ANALISIS PERSEPSI KONSUMEN TERHADAP KEPUTUSAN MEMBELI ULANG PRODUK KUOTA IM3 OOREDOO DI KOTA BANJARMASIN - Jamaluddin Jamaluddin (At-Tadbir : jurnal ilmiah manajemen, 2020)
The study aims to determine the effect of consumer perception factors that can influence the decision to repurchase IM3 Ooredoo products to consumers in the city of Banjarmasin. The factors of consumer perception examined include Price, Service Quality, Location, Personal and Stimulus. The population of the study is all Banjarmasin city residents who use the IM3 Ooredoo Quota. Samples were taken with a non-probability sampling method with a sampling quota of 125 samples. By using a questionnaire with a Likert scale method. The statistical test method uses Multiple Linear Regression Analysis, with the hypothesis testing of the t statistical test and the F statistical test. The results of the analysis based on the use of all independent variables indicate that consumers' perceptions namely Price, Service Quality, Location, Personal and Stimulus together are able to influence Buying Decisions Repeat IM3 Ooredoo Quota Products in Banjarmasin City. While partially only stimulus variables are not able to show a significant relationship with the variable Repurchase Decision of IM3 Ooredoo Products in Banjarmasin City.Keywords: Price, Service Quality, Location, Personal, Stimulus, Repurchase Decision